Family Background Influence and Participation in Extracurricular Activities on Students' Attitudes of Nationalism - Ardiyansyah, Hidayat; Supriyono, Supriyono; Sukriono, Didik (Jurnal Pendidikan Humaniora, 2020)
Abstract: This study aims to determine the differences in attitudes of nationalism in terms of various types of extracurricular activities and the relationship between the intensity of extracurricular participation with students' attitudes of nationalism. This research was a comparative and correlational quantitative research The data collection technique used a questionnaire. The data analysis technique used normality test, difference test, regression test and correlation test. There is a significant difference in the attitude of nationalism in terms of various extracurricular activities due to the Sig. 0.014 or <0.05. The intensity data of participation in extracurricular activities has a value smaller than the respective r table, it is concluded that there is no relationship between the intensity of participation in extracurricular activities with the attitude of nationalism.Keywords:Â family background, extracurricular activities, student participation, attitude, nationalismAbstrak: Penelitian ini bertuan untuk mengetahui perbedaan sikap nasionalisme ditinjau dari berbagai jenis kegiatan ekstrakurikuler dan hubungan antara intensitas keikutsertaan ekstrakurikuler dengan sikap nasionalisme siswa. Penelitian ini berjenis penelitian kuantitatif komparatif dan korelasional. Dengan sampel sebanyak 355 siswa di 7 SMA Negeri Kota Malang. Data diambil menggunakan kuesioner. Analisis data yang digunakan adalah uji normalitas, uji beda, uji regresi dan uji korelasi. Terdapat perbedaan secara signifikan sikap nasionalisme ditinjau dari berbagai macam kegiatan ekstrakurikuler dikarenakan nilai Sig. Sebesar 0,014 atau <0,05. Data intensitas keikutsertaan dalam kegiatan ekstrakurikuler mempunyai nilai lebih kecil dari r tabel masing-masing, disimpulkan bahwa tidak terdapat hubungan antara intensitas keikutsertaan dalam kegiatan ekstrakurikuler dengan sikap nasionalisme.Kata kunci:Â latar belakang keluarga, aktifitas ekstrakurikular, partisipasi siswa, sikap, nasionalisme